An Evidence‐Based Approach to Breastfeeding Neonates at Risk for Hypoglycemia. Issue 1 (January 2014) - Csont, Georgia Lowmaster; Groth, Susan; Hopkins, Patrick; Guillet, Ronnie
ABSTRACT The revised standard of care for breastfeeding infants at risk of developing hypoglycemia during transitioning to extrauterine life was developed using the American Academy of Pediatrics (AAP) 2011 hypoglycemia guidelines, the Academy of Breastfeeding Medicine protocol, and staff input. A pre/postimplementation chart audit indicated support of infant safety by glucose stabilization, breastfeeding within the first hour of life, and breastfeeding frequency without an increase in blood sampling, formula use, or admissions to the special care nursery.